2013
DOI: 10.3109/1040841x.2012.754401
|View full text |Cite
|
Sign up to set email alerts
|

Allergic bronchopulmonary mycosis due to fungi other thanAspergillus: a global overview

Abstract: Allergic bronchopulmonary mycosis (ABPM) is a hypersensitivity-mediated disease of worldwide distribution. We reviewed 143 reported global cases of ABPM due to fungi other than aspergilli. The commonest etiologic agent was Candida albicans, reported in 60% of the cases, followed by Bipolaris species (13%), Schizophyllum commune (11%), Curvularia species (8%), Pseudallescheria boydii species complex (3%) and rarely, Alternaria alternata, Fusarium vasinfectum, Penicillium species, Cladosporium cladosporioides, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
126
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(139 citation statements)
references
References 128 publications
3
126
0
3
Order By: Relevance
“…In the present study, precipitating antibodies against the colonizing mold were demonstrated for 41% of patients by the Ouchterlony immunodiffusion method. Although immunoprecipitation testing remains the standard approach for diagnosing previous or continued exposure/sensitization to mold antigens, it fails to differentiate between previous exposure and the cause of disease (30)(31)(32). Antifungal therapy could reduce the effects of antigen exposure by eradicating the colonizing mold (29,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, precipitating antibodies against the colonizing mold were demonstrated for 41% of patients by the Ouchterlony immunodiffusion method. Although immunoprecipitation testing remains the standard approach for diagnosing previous or continued exposure/sensitization to mold antigens, it fails to differentiate between previous exposure and the cause of disease (30)(31)(32). Antifungal therapy could reduce the effects of antigen exposure by eradicating the colonizing mold (29,32).…”
Section: Discussionmentioning
confidence: 99%
“…Although immunoprecipitation testing remains the standard approach for diagnosing previous or continued exposure/sensitization to mold antigens, it fails to differentiate between previous exposure and the cause of disease (30)(31)(32). Antifungal therapy could reduce the effects of antigen exposure by eradicating the colonizing mold (29,32). Recently, the efficacy of antifungal drugs for treatment of atopic cough, fungusassociated chronic cough, and allergic fungal cough induced by basidiomycetous fungi has been reported (28,29,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Most cases were reported in India (47%) followed by Japan. The median IgE value was threefold higher than that of ABPA, indicating that these fungi may elicit a stronger immunological response than Aspergillus (20).…”
Section: Discussionmentioning
confidence: 85%
“…Patients manifested a serious of symptoms such as chills, fever, asthma, cough, mucus sputum, hemoptysis and chest pain in the clinical. Type of allergy can cause breathing difficulties and asthma [18]. Results of X-ray examination showed infiltration of lung, lesions of cavity, round shadow with clear border which can drift with movement of body position.…”
Section: Discussionmentioning
confidence: 99%
“…Infected vessels of lung can cause formation of thrombosis and hemorrhagic infarction. Therefore, ground-glass-like changes, nodules and cavity with inserted nodules are widely fund, but cavity without inserted nodule is seldom observed in clinical [18,19].…”
Section: Discussionmentioning
confidence: 99%